Generational differences in the workplace: A review of the evidence and directions for future research. (17th December 2013) - Lyons, Sean; Kuron, Lisa; Hodgkinson, Gerard P.; Ford, J. Kevin
Summary Generational differences in the workplace have been a popular topic over the past two decades, generating a volume of articles, book chapters and books. We critically review the research evidence concerning generational differences in a variety of work‐related variables, including personality, work values, work attitudes, leadership, teamwork, work–life balance and career patterns, assess its strengths and limitations, and provide directions for future research and theory. Our review indicates that the growing body of research, particularly in the past 5 years, remains largely descriptive, rather than exploring the theoretical underpinnings of the generation construct. Evidence to date is fractured, contradictory and fraught with methodological inconsistencies that make generalizations difficult. The results of time‐lag, cross‐temporal meta‐analytic and cross‐sectional studies provide sufficient "proof of concept" for generation as a workplace variable, but further theoretical and qualitative work is needed to flesh out mediators and moderators in the relationship between generation and work‐related variables. We conclude by arguing for a more nuanced and theoretical research agenda that views generation as a social force in organizations rather than as merely a demographic variable. We also call for qualitative research, greater consideration of context and more methodological rigor. Copyright © 2013 John Wiley & Sons, Ltd.